First description of the female Elimaea melanocantha (Walker, 1869) (Orthoptera: Tettigoniidae: Phaneropterinae) from India - Swaminathan, R.; Nagar, Rajendra; Swaminathan, T. (Zootaxa, 2017)
The genus Elimaea Stal, 1874 was established for the type species Phaneroptera subcarinata Stal 1861 (Hongkong), the type genus of the Phaneropterinae. These insects are poorly known from India. Relevant important work on the taxonomy and distribution of Tettigoniidae of northeastern India include those of Barman & Srivastava (1976), Shishodia (2000), Shishodia & Tandon (2000), Barman (2003), Shishodia et al. (2003 & 2010) and, recently, Nagar et al. (2014, 2015a-b) have reported new and additional species of Phaneropterinae from India. The tribe Elimaeini Yakobson, 1905 (group Elimaeae Brunner, 1878) is known to comprise three Oriental genera, Elimaea Stal, 1874; Hemielimaea Brunner, 1878; and Ectadia Brunner, 1878. Karny (1926) divided the genus into three subgenera: Orthelimaea, Rhaebelimaea and Elimaea s. str., based on the shape of the anterior femora and the branching in the radius sector of the tegmen. Of these, Elimaea is most speciose and quite widespread in the Indian sub-continent. Gorochov (2013) reported two species, Elimaea melanocantha (Walker, 1869) and Elimaea nigrosignata Bolivar, 1900 in the group Neoelimaea. The terminology used is that of Ingrisch (1998) and Rentz and Colless (1990).